Association of specific HLA alleles and haplotypes with pemphigus vulgaris in the Bulgarian population - Drenovska, Kossara; Ivanova, Milena; Vassileva, Snejina; Shahid, Martin Abu; Naumova, Elissaveta (Frontiers in Immunology, 2022)
Pemphigus vulgaris (PV) is an autoimmune bullous dermatosis with uneven geographic distribution and higher incidence in certain populations. In previous studies, a relatively high incidence of PV was reported in Bulgaria (0.47/100000/year) comparable to that in other countries. The genetic background was considered responsible for the disease susceptibility and multiple reports have proven PV to be a HLA-associated condition. The aim of our study was to analyze the role of genetic factors in the development of PV in Bulgaria. HLA-genotyping was performed in fifty-six PV patients, ethnic Bulgarians whose diagnosis was confirmed based on clinical, histological, and immunofluorescent findings. The control group consisted of 204 healthy individuals from the Bulgarian population without evidence for HLA-associated autoimmune diseases. HLA-A,-B,-DRB1,-DQB1 analysis was performed by PCR-SSP. Our results revealed predisposing associations with DRB1*14, DRB1*04:02, B*38, B*55, while allele DRB1*03:01 and the corresponding haplotypes were significantly decreased in the PV patients. The predisposing role of these alleles has been observed in other populations. All reported predisposing DRB1 alleles have the same amino acids at key positions of the beta chain of the HLA molecules: 26 (Phe), 67 (Leu or Ileu), 70 and 71 (hydrophobic AA: Gln, Arg, Asp or Glu), and 86 (Val), which is important for the selective presentation of desmoglein 3-peptides. Additionally, specific alleles HLA-A*01 and DRB1*11 were identified with decreased frequencies in the patients’ group, the last one being a common protective allele for autoimmune diseases in the Bulgarian population. The elucidation of the role of genetic factors for the development of pemphigus will help explain its higher incidence and clinical variability in certain populations.